2021
DOI: 10.1155/2021/5899356
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Shear Strength in FRP‐Reinforced Concrete Beams Using Bat Algorithm‐Based Artificial Neural Network

Abstract: In this article, 140 samples with different characteristics were collected from the literature. The Feed Forward network is used in this research. The parameters f’c (MPa), ρf (%), Ef (GPa), a/d, bw (mm), d (mm), and VMA are selected as inputs to determine the shear strength in FRP-reinforced concrete beams. The structure of the artificial neural network (ANN) is also optimized using the bat algorithm. ANN is also compared to the Genetic Algorithm (GA) and Particle Swarm Optimization (PSO) algorithm. Finally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Based on the equilibrium of forces in a cross-section of a beam at failure, Pellegrino and Moderna [14] have obtained a theoretical equation for effective FRP strain. Nehdi et al [15], [16], and Kara [17] have taken a genetic algorithm approach whereas Hosseini and others [18], [19], [20], [21] have adopted machine learning and neural networks. Anvari et al [22] have also used an evolutionary machine learning approach, named genetic expression programming.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the equilibrium of forces in a cross-section of a beam at failure, Pellegrino and Moderna [14] have obtained a theoretical equation for effective FRP strain. Nehdi et al [15], [16], and Kara [17] have taken a genetic algorithm approach whereas Hosseini and others [18], [19], [20], [21] have adopted machine learning and neural networks. Anvari et al [22] have also used an evolutionary machine learning approach, named genetic expression programming.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the developed model has more robustness than the classical SVR model and empirical equations. Nikoo et al 46 integrated bat algorithm with ANN to estimate shear behavior of FRB reinforced concrete elements. Based on the statistical assessment and comparison with other optimization algorithms, the study confirmed that the integrated model attained more accurate results than particle swarm optimization (PSO) and genetic algorithm (GA).…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous advancement of computer technology, artificial intelligence (AI) techniques represented by machine learning (ML) models are increasingly applied in the field of civil engineering, particularly in the prediction of the performance of RC beams [21][22][23][24][25][26][27][28][29][30]. Mansour et al [31] utilized the artificial neural network (ANN) model to predict the shear performance of RC beams.…”
Section: Introductionmentioning
confidence: 99%